El género Sternbergia (Amaryllidaceae): en la Península Ibérica - Ramón Morales; Juan Castillo (Anales del Jardín Botánico de Madrid)
The genus Sternbergia is studied in the Iberian Peninsula. Color drawings of the two Iberian species and distribution maps are given for the studied area. Sternbergia lutea has been traditionally cultivated and it is now naturalized in the Iberian Peninsula.